Is the accounting quality after the mandatory adoption of IFRS a random walk? Evidence from Europe. Issue 3 (10th September 2018) - Morais, Ana Isabel; Fialho, Ana; Dionísio, Andreia
Abstract : Purpose: The purpose of this paper is to provide empirical evidence regarding the classification of European countries based on accounting quality metrics. The authors investigate whether the grouping of countries based on accounting quality levels differs from other classifications based on accounting practices or country-specific factors identified in previous studies. Design/methodology/approach: The authors run panel data regressions for 2.078 European listed companies using value relevance and earnings smoothing metrics. The authors also apply cluster analysis to classify the countries. Findings: The results suggest that the adoption of a common set of International Financial Reporting Standards (IFRS) did not lead to a similar level of accounting quality of financial information. The authors identified three clusters of countries that are not coincident with previous classifications. Research limitations/implications: The results show that the adoption of different accounting practices allowed in IFRS does not necessarily influence accounting quality. Practical implications: The results suggest that the way regulators decided to incorporate IFRS into national accounting systems is one issue that may be relevant in explaining the three clusters. Originality/value: The paper provides empirical evidence that supports two theoretical assertions. The first is that a classification depends entirely on the characteristics used to represent the countries being classified. The second is that the adoption of a single set of accounting standards does not determine similar accounting practices and does not lead to similar levels of accounting quality.